Treatment of pediculosis capitis - Prashant Verma; Chaitanya Namdeo (Wolters Kluwer Medknow Publications, 2015)
An endeavour to delineate the salient details of the treatment of head lice infestation has been made in the present article. Treatment modalities including over the counter permethrin and pyrethrin, and prescription medicines, including malathion, lindane, benzyl alcohol, spinosad are discussed. Salient features of alternative medicine and physical treatment modalities are outlined. The problem of resistance to treatment has also been taken cognizance of.